2015
DOI: 10.1002/chin.201543113
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Antifungal Activity of Novel Furan‐2,4‐dione Derivatives Containing Substituted Phenylhydrazine Moiety.

Abstract: Among the title compounds, derivative (Vb) shows excellent bioactivity with an EC50 value markedly lower than the commercial fungicide procymidone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The title compounds, that is, phenylhydrazine-substituted tetronic acid derivatives, were synthesized and recrystallized using the reported method. [28] The structure information of these compounds were obtained from our previous study [27][28][29] and shown in Table 1. Considering that the compounds 23-26, 29, and 31 have not been published, the characterization information of these compounds were given in supporting information.…”
Section: Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…The title compounds, that is, phenylhydrazine-substituted tetronic acid derivatives, were synthesized and recrystallized using the reported method. [28] The structure information of these compounds were obtained from our previous study [27][28][29] and shown in Table 1. Considering that the compounds 23-26, 29, and 31 have not been published, the characterization information of these compounds were given in supporting information.…”
Section: Chemicalsmentioning
confidence: 99%
“…The title compounds were screened for the antifungal activity in vitro against Fusarium graminearum (FUS), BOT, RHI, and Colletotrichum capsici (COL) using the radial growth inhibition technique. [30] The antifungal activity was obtained from our previous study [27] and expressed as EC 50 values (μg/ml), which were shown in Table 2.…”
Section: Antifungal Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations